Groundwater productivity analysis with geology in the Geumgang River region, Korea - Moon, Sang-Ho; Park, Changhui; Kim, Hyoung Chan; Kim, Yongcheol; Kee, Weon-Seo; Lee, Chung-Mo; Kim, Sunghyun (Geosciences journal (Seoul, Korea), 2024)
This study examined hydrogeological factors, including specific capacity, transmissivity and hydraulic conductivity, in the Geumgang River region of South Korea. A total of 4,329 well data (3,337 from bedrock aquifers and 992 from alluvial and weathered soil/rock aquifers) were collected from the basic groundwater survey reports and validated. To analyze geology-related ground-water productivity in this study, specific capacity and transmissivity data of nine geological units were considered. Alluvial and weathered soil/rock aquifer wells exhibited average specific capacity and transmissivity values of 147 m 3 /day/m and 84.1 m 2 /day, respectively. Meanwhile, bedrock aquifer wells showed average specific capacity and transmissivity values of 13.4 m 3 /day/m and 13.0 m 2 /day, respectively. Notably, in terms of specific capacity and transmissivity, alluvial and weathered soil/rock aquifer wells were more productive than bedrock aquifer wells. In case of bedrock aquifers, non-porous volcanic rocks and Cretaceous igneous intrusive rocks showed relatively low productive features and meta-sedimentary rocks showed higher productivity than other geological units. Box plot analysis for logarithmic specific capacity values was used to decide the criteria for groundwater productivity of wells. For bedrock aquifer wells, this study suggested that the lower whisker (−0.413), 1/4 quartile (0.457), 3/4 quartile (1.05), and upper whisker (1.94) can be used as the criteria for very low, low, moderate, high, and very high productivity. Spatial statistical analyses using kernel density and optimized hot spot methods identified several potential sites for large-capacity groundwater development with high probability. These hot spots are located in crystalline gneisses at Gongju-Sejong area, in Triassic-Jurassic intrusive igneous rocks at Gimje-Jeongeup and Boeun areas, and in meta-sedimentary rocks at Nonsan-Geumsan, Yeongdong, Boeun and Hongseong areas. Specifically, the Okcheon meta-sedimentary rocks aquifer, which is a significant bedrock aquifer in the Geumgang River region and widely distributed throughout the Okcheon Belt, was suggested as a prime candidate for groundwater development. Major aquifers in Okcheon meta-sedimentary rocks are closely associated with intercalated thin beds of brittle quartzite or carbonate rocks with dissolved cavities. The Jurassic granites aquifer can also be served as another important bedrock and/or alluvial and weathered soil/rock aquifers in the Geumgang River region, owing to its widespread distribution and moderate groundwater-yielding productivity. This aquifer type is related to the development of a stratiform fissured layer and an upper saprolite part due to weathering processes.